Heterometallic Dual-Liganded AE-Ln-CPs Luminescent Probes for Efficient Sensing of Fe(III) Ions - Hou, Jieqiong; Chen, Yanmei; Zou, Shuixiang; Dong, Wenwen; Ju, Zhenghua; Lin, Junqi; Ruan, Zhijun; Liu, Shanshan; Tian, Zhengfang (Frontiers in Chemistry, 2022)
Iron ion is widely present in the environment and in biological systems, and are indispensable trace elements in living organisms, so development of an efficient and simple sensor for sensing Fe(III) ions has attracted much attention. Here, six heterometallic AE-Ln coordination polymers (CPs) [Ln2(pda)4(Hnda)2Ca2(H2O)2]·MeOH (Ln = Eu (1), Tb (2); H2pda = 2,6-pyridinedicarboxylic acid, H2nda = 2,3-naphthalenedicarboxylic acid), [Ln(pda)2(nda)AE2(HCOO)(H2O)] (AE = Sr, Ln = Eu (3), Tb (4); AE = Ba, Ln = Eu (5), Tb (6)) with two-dimensional (2D) layer structures were synthesized by hydrothermal method. All of them were characterized by elemental analysis, XRD, IR, TG, as well as single crystal X-ray diffraction. They all show infinite 2D network structure, where complexes 1 and 2 are triclinic with space group of P_1 ̅ , while 3-6 belong to the monoclinic system, space group P21/n. The solid-state fluorescence lifetimes of complexes 1, 3 and 5 are τobs1 = 1930.94 , 2049.48 and 2413.04 μs, respectively, and the quantum yields Фtotal are 63.01%, 60.61%, 87.39%, respectively, which are higher than those of complexes 2, 4 and 6. Complexes 1-6 all exhibited efficient fluorescence quenching response to Fe3+ ions in water, and were not interfered by the following metal ions: Cu2+, Cd2+, Mg2+, Ni2+, Co2+, Ca2+, Ba2+, Sr2+, Li+, Na+, K+, Al3+, Fe2+, Pb2+, Cr3+, Mn2+ and Zn2+. The quenching coefficient KSV for complexes 1-6 is 1.41×105 M−1, 7.10×104 M−1, 1.70×105 M−1, 1.57×105 M−1, 9.37×104 M−1, 1.27×105 M−1, respectively. The fluorescence quenching mechanism of these complexes towards Fe3+ ions was also investigated. It is possible that the weak interaction formed between the complexes and the Fe3+ ions reduce the energy transfer from the ligand to the Ln3+ ion, producing the emission burst effect. This suggests that complexes 1-6 can be candidate for efficient luminescent sensor of Fe3+.